Assessing Rollover Criteria for EUAs and CERs - Carchano, Oscar; Medina, Vicente; Pardo, Angel (International Journal of Economics and Financial Issues, 2014)
ABSTRACT: This study discusses how to roll over European Union Allowances (EUAs) and Certified Emissions Reduction (CERs) futures contracts with different maturities. The aim is to elucidate whether or not the choice of rollover date is important when constructing EUAs and CERs continuous futures time series. We have applied five different methodologies to link the series and our findings indicate that return distributions do not significantly differ for the different criteria. This result has direct practical implications in the field of applied econometrics of carbon markets given that we prove that the selection of the simple last-day rollover methodology criterion has no downside not only in terms of returns distribution but also with respect to liquidity levels. Keywords: Rollover date; European Union Allowances (EUAs); Certified Emission Reductions (CERs). JEL Classification: G1